Simulation of the flow around an oscillating cylinder with adaptive lattice Boltzmann methods - (:unkn) unknown (Civil-Comp Press, 2017)
As an alternative to the popular approach of solving the Navier-Stokes equations on unstructured, triangular meshes, we utilize in here primarily the self-developed parallel adaptive lattice Boltzmann code AMROC-LBM to study laminar and turbulent flow over an oscillating and rotating cylinder in two space dimensions at Reynolds number 1322 and 6610, respectively. The method is implemented on a dynamically adaptive Cartesian finite volume grid and considers geometrically complex boundaries with a level-set-based ghost-fluid-type approach, making the code well suited for moving structures. Predicted vortex shedding downstream is found to be in good agreement with available experimental results. A direct comparison to the commercial code XFlow shows that AMROC-LBM provides more reliable predictions in shorter computational time. © Civil-Comp Press, 2017.
Keywords: AMROC; Block-structured parallel adaptive mesh refinement; Large-eddy simulation; Lattice Boltzmann method; Oscillating cylinder; XFlow